2016
DOI: 10.3389/fnbeh.2016.00233
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral Consequence of Phenylketonuria in Mice Depends on the Genetic Background

Abstract: To unravel the role of gene mutations in the healthy and the diseased state, countless studies have tried to link genotype with phenotype. However, over the years, it became clear that the strain of mice can influence these results. Nevertheless, identical gene mutations in different strains are often still considered equals. An example of this, is the research done in phenylketonuria (PKU), an inheritable metabolic disorder. In this field, a PKU mouse model (either on a BTBR or C57Bl/6 background) is often us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
5
21
0
Order By: Relevance
“…In addition, distance moved and velocity during the Open Field Test showed that 18-day-old ENU2 pups had lower general activity than age-matched WT. These data are in agreement with several previous studies showing reduced locomotor activity in adult animal model of PKU [ 24 , 34 , 35 , 43 ] and underline the precociousness of the deficit.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, distance moved and velocity during the Open Field Test showed that 18-day-old ENU2 pups had lower general activity than age-matched WT. These data are in agreement with several previous studies showing reduced locomotor activity in adult animal model of PKU [ 24 , 34 , 35 , 43 ] and underline the precociousness of the deficit.…”
Section: Discussionsupporting
confidence: 93%
“…In a murine model of a metabolic inherited disease it is essential to analyze behavioral and neurochemical phenotyping during the early developmental period in order to identify the exact onset of behavioral symptoms and brain alterations, and then to indicate the best time for early intervention and what parameters to keep an eye on during preclinical evaluation of experimental treatments. To date, although behavioral and neurochemical alterations have been extensively demonstrated in adult mice [ 34 , 43 ], this study is the first to report the onset of these deficiencies, providing a comprehensive behavioral and neurochemical assay of the developing ENU2 mouse, the best murine model of PKU. Our study shows that ENU2 mice reach many developmental milestones later than their healthy littermates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The balance beam is a sensorimotor integration test, which focuses on hind limb functioning. 30 In our lab, this test has been proven to be sensitive to the effects of disease phenotype, 31 exercise 32 and also WBV stimulation, 11 in different mouse strains. This test was, therefore, included as a control for the effectiveness of the WBV protocol in this experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Both genetic strains of the PKU mouse model have a point mutation in the gene encoding for phenylalanine hydroxylase causing Phe to rise in blood and brain (10). The PKU model was originally described for the BTBR background but the model was latter crossed back on to the C57Bl/6J background.…”
Section: Methodsmentioning
confidence: 99%